Implementasi Algoritme Trivium Untuk Mengamankan Komunikasi Data Master-Slave Pada Perangkat Berbasis Modul Komunikasi NRF24L01 - Sara Yosephina; Adhitya Bhawiyuga; Ari Kusyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet of Things (IoT) is a network concept that connects various devices so that these devices can produce services and cooperate with each other to achieve common goals. Security is one of the weaknesses of IoT implementation. Trivium algorithm is a hardware-side security candidate by the eSTREAM Project organized by NIST. Trivium algorithm architecture has a complex level of complexity and does not require large power so it is suitable for use on devices that have low power. This study explains how to utilize the Trivium algorithm to secure data communication using NRF24L01. There are 5 tests performed including validation test vector, performance analysis through the validation time keystream and data encryption ecryption, performance analysis of delivery time from master to slave using communication module NRF24L01, and testing with sniffing. Results of this resesarch indicate that the keystream validation in accordance with test vector. The performance of encryption processing time has an average of 695.8 ms for 8 bit data size, 951.2 ms for 16 bit data size and 1460.2 ms for 32 bit data size. And the results of the decryption processing time performance have an average of 443.5 ms for 8 bit data size, 447.8 ms for 16 bit data size and 448.4 ms for 32 bit data size. And the results of the test by sniffing shows that the Trivium algorithm can perform data encryption well with the sniffing process can only sniff the data that has been encrypted.